MATEMATIKA DALAM AL-QUR’AN - nasution, ali anas (IAIN PADANGSIDIMPUAN, 2013)
AbstrakExistence of integration between science and religion, seen with existence of very mathematical calculation in al-Qur'an. moment of Al-Qur'an degraded by 14 last century, system writing of recognized number now there is no. Instead, letters used as by device for the number ofFormation of Al-Quran which consist of 114 letter, 30 juz, 6666 sentence, 29 letter of Fawatih and 85 letter is not Fawatih, 86 letter of Makkiyah and 28 letter of Madaniyah, existence of 30 sentence of Muqhatta'At, 78 letter in 14 sentence combination of muqhatta'at and existence of 30 number of[is so-called expressly in Al-Quran, altogether become part of security system ( sophisticated kriptografi) which there no creature satupun can make it, more than anything else contesting it. And so do number 0 (nol) - cikal will revolutionize science, specially computer, is in the reality mentioned manifestly in the form of sentence composition anomaly of Basmallah. Open to altogether [pass/through] a key public ( public key) number 19 like expressed in letter of Al-Muddatsir sentence 30-31And wide open balance secret progressively when prime number emerge in composition of Al-Quran. That Numbers continue berhamburan lay open the truth of Al-Quran which is on finally have estuary to Tauhid, that Allah of lah degrading Al-Quran and looking after it from human being interference through role of number as tentara-tentara-Nya which there no its equifinality. Then what it is true there is mathematics in al-Qur'an? this Simple article will try to answer question above, Insya Allah